Peranan Kantor Jasa Penilai Publik (KJPP) Dalam Kegiatan Pengadaan Tanah Untuk Kepentingan Umum (Antara Profesionalisme Dan Perbuatan Melawan Hukum/Tindak Pidana Korupsi) - Dahnir Dahnir; Muhammad Yamin; Alvin Syahrin; Sutiarnoto Sutiarnoto (Iuris Studia: Jurnal Kajian Hukum, 2022)
The basic provisions of the legislation governing the authority of the Appraiser/KJPP to conduct assessments in land acquisition for the public interest are only Article 31 to Article 34 of Law no. 2 of 2012 concerning Land Acquisition for Development in the Public Interest. In the regulatory setting that regulates the Appraiser/KJPP there are no criminal provisions for each party involved in the assessment, so that criminal liability between the appraiser and KJPP and the parties involved in the assessment is not balanced and fair, so that legal certainty and legal justice are not achieved. There are no regulations governing criminal responsibility for the Appraiser/KJPP, so there is no criminal responsibility between the Appraiser as an individual and the KJPP as a corporation